(untitled) (REVISTA NODO, 2024)
Anna Maria Guasch has dedicated her life to art criticism and history. Professor emeritus, from her work as a professor of global art history and art criticism at the University of Barcelona, ​​she has built a career in which she alternates interaction with her students and with artists and art curators. This coming and going between academia and the art world has been fertile ground for the development of a unique practice in art history. Her curiosity and commitment to exhaustive research on the topics she works on have led her to travel outside of Europe. Her contact with the school of contemporary art thinkers from the October and Third Text magazine school positioned her as a significant bridge between the information that was being generated in the global north and the reflections that were made on this thought in Latin America. Every time he exhausted one song during his career he moved with the same enthusiasm to the next. Currently his work is focused on new eco-environmental knowledge. This conversation is a testament to his legacy in the field of art history and criticism, where he has given important weight to the concept of context without falling into the trap of defending the local. His contribution to the discipline to this day lies in a flexible, interdisciplinary, dialogic and contemporary vision of what it can be to talk, write and think about art.